Restoring the Angiogenic Capacity of the Human Diabetic Adipose-derived mesenchymal stem cells Primed with Deferoxamine as a Hypoxia Mimetic Agent: Role of HIF-1α - Raziye Tajali; Akram Eidi; Hosein Ahmadi Tafti; Abdolreza Pazouki; Ali Mohammad Sharifi (Tabriz University of Medical Sciences, 2023)
Purpose: Insufficient angiogenesis is associated with serious diabetic complications. Recently, adipose-derived mesenchymal stem cells (ADScs) are known to be a promising tool causing therapeutic neovascularization. However, the overall therapeutic efficacy of these cells is impaired by diabetes. This study aims to investigate whether in vitro pharmacological priming with deferoxamine, a hypoxia mimetic agent, could restore the angiogenic potential of diabetic human ADSCs. Methods: Diabetic human ADSCs were treated with deferoxamine and compared to normal and nontreated diabetic ADSCs for the expression of hypoxia inducible factor 1-alpha (HIF-1α), vascular endothelial growth factor (VEGF), fibroblast growth factor-2 (FGF-2) and stromal cell-derived factor-1α (SDF-1α), at mRNA and protein levels, using qRT-PCR, western blotting and ELISA assay. Activities of matrix metalloproteinases (MMPs)-2 and -9 were measured using a gelatin zymography assay. Angiogenic potentials of conditioned media derived from normal, Deferoxamine treated, and non-treated ADSCs were determined by in vitro scratch assay and also three-dimensional tube formation assay. Results: It is demonstrated that deferoxamine (150 and 300 μM) stabilized HIF-1α in primed diabetic ADSCs. At the concentrations used, deferoxamine did not show any cytotoxic effects. In deferoxamine treated ADSCs, expression of VEGF, SDF-1α, FGF-2 and the activity of MMP-2 and MMP-9 were significantly increased compared to nontreated ADSCs. Moreover, deferoxamine increased the paracrine effects of diabetic ADSCs in promoting endothelial cell migration and tube formation. Conclusion: Deferoxamine might be an effective drug for pharmacological priming of diabetic ADSCs to enhance the expression of proangiogenic factors noted via HIF-1α accumulation. In addition, impaired angiogenic potential of conditioned medium derived from diabetic ADSCs was restored by deferoxamine.